2003
DOI: 10.1042/bj20030578
|View full text |Cite
|
Sign up to set email alerts
|

Studies on G-protein α·βγ heterotrimer formation reveal a putative S-prenyl-binding site in the α subunit

Abstract: The alpha and betagamma subunits of heterotrimeric G-proteins contain specific lipid modifications, which are required for their biological function. However, the relevance of these modifications to the interactions within the heterotrimeric G-protein is not fully understood. In order to explore the role of the S-prenyl moiety of the isoprenylated betagamma dimer of retinal transducin, betagamma(t), in the formation of the heterotrimeric complex with the corresponding N-acylated alpha subunit, alpha(t), we emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
(81 reference statements)
1
17
0
Order By: Relevance
“…Although protein prenylation may facilitate anchoring of proteins to lipid membranes, data suggesting its role in protein interaction and activation are accumulating (12,17,19,28,30,38). Our data support the proposition of Magee and Seabra (26), which stresses the role of prenyl groups in protein- protein FIG.…”
Section: Discussionsupporting
confidence: 83%
“…Although protein prenylation may facilitate anchoring of proteins to lipid membranes, data suggesting its role in protein interaction and activation are accumulating (12,17,19,28,30,38). Our data support the proposition of Magee and Seabra (26), which stresses the role of prenyl groups in protein- protein FIG.…”
Section: Discussionsupporting
confidence: 83%
“…The prenyltransferases contain a common ␣ subunit and one of two different ␤ subunits that confer specificity for either farnesyl or geranylgeranyl addition. Although the prenyl group typically anchors the protein to the plasma membrane, recent studies showed that it can also act as a "greasy finger" to enhance protein-protein interactions (23). Scans of various eukaryotic genomes indicate that many proteins are potential prenylation targets (Ͼ100 in Arabidopsis thaliana (24)).…”
mentioning
confidence: 99%
“…In this issue of the Biochemical Journal, Dietrich et al [31] report a similar approach, where prenylcysteine analogues have been shown to directly inhibit interaction between transducin α-subunit and the geranylgeranyl group of the γ -subunit. Both farnesyl and geranylgeranyl derivatives were effective, and inhibition was competitive and reversible.…”
mentioning
confidence: 99%